(untitled) (UNED Research Journal, 2017)
The present study aimed to investigate the changes of bigeye kilka Clupeonella grimmi population caused by human and natural factors in southern waters of the Caspian Sea. This study was conducted in 2009 and 2010 during which Length, weight and age were studied. The annual survival rate, natural and fishing mortality in 2009 were estimated 0.305 yr-1, 0.448 yr-1 and 0.736 yr-1, and in 2010 were 0.309 yr-1, 0.419 yr-1 and 0.775 yr-1, respectively. Accordingly, total mortality in 2009 and 2010 was 1.184 yr-1 and 1.174 yr-1 and the exploitation rate was calculated 0.621 and 0.660, respectively. Bigeye kilka appropriated 4.5% and 4.2% of total kilka catch in Mazandaran Province in 2009 and 2010, respectively. Results showed that bigeye kilka catch amount has decreased and its population is under over-fishing and natural pressure.